Effect of the addition of fly ash on the specific methane production and microbial communities in the anaerobic digestion of real winery wastewater. Issue 10 (13th July 2021) - Lauzurique, Yeney; Fermoso, Fernando G; Sánchez, Nicolás; Castillo, Alejandra; Valdés, Natalia; Tello, Mario; Salazar, Ricardo; García, Verónica; Huiliñir, César
Abstract: BACKGROUND: Fly ash is an important source of trace elements that can act as cofactors of enzyme systems and improve anaerobic digestion processes. However, its effect on anaerobic digestion using real wastewater has not yet been studied. In the present work, the effect of fly ash on the anaerobic digestion of real winery wastewaters was studied, by means of specific methanogenic activity assays and with a special focus on its effect on the specific methane production and the microbial communities present. Five fly ash concentration (25, 50, 75, 100, and 150 mg L −1 ) were supplemented under mesophilic conditions. RESULTS: The results showed that 25 mg L −1 of fly ash improved the specific methane production by 18% compared to the control assay; meanwhile, a concentration of 100 mg L −1 of fly ash generated inhibition of the methanogenesis and a 20% specific methane production decrease with respect to the control experiment. The microbial community analysis verified that fly ash supplementation affected the bacterial communities, with a significant effect on acetogenic bacteria, such as Cloacimonetes and Firmicutes . CONCLUSION: The addition of adequate concentrations of fly ash to the process can raise the relative abundance of some microorganisms and, consequently, could increase the specific methane production in the anaerobic digestion of winery wastewater. © 2021 Society of Chemical Industry (SCI).